Bahasa Inggris Bahasa Inggris: Bahasa Indonesia - Venanda Hermawati; Sigit Yulianto (Jurnal Penelitian Pendidikan IPA, 2025)
This research applied Borg and Gall's research and development (R&D) method. There are 10 stages, but this research only reaches stage 8, namely the usage trial. The difficulty experienced by students in learning the material is due to the lack of technology-based media so that the value of complete students is 35 and 65% is not complete. The data collection methods used are tests and non-tests (observation, interviews, questionnaires, and documentation). This is the main reason for this research, which is to make learning media based on Google Sites, test its feasibility, and evaluate its effectiveness. The results showed that Google Sites-based media was created using Google Sites, with contents in the form of a main page, main menu (learning objectives, materials, LKPD, videos, music, and profile), and navigation guides. A very feasible assessment was obtained with a percentage of 93.75% material experts and 92.5% media experts. The effectiveness of the media is measured from the pretest and posttest scores as evidenced by the calculation of the t value of -10.699 and the sig value. (2-tailed) of 0.000 < 0.05. The N-Gain test obtained a medium category with an average N-Gain result of 0.6154. The results of this study indicate that the media design has been made, feasible, and effective to improve the learning outcomes of fifth grade students of SDN Rejamulya 02 Cilacap Regency on the material of Sound and its Properties.